Meningkatkan Keaktifan Belajar Dan Hasil Belajar Peserta Didik Mata Pelajaran Akidah Akhlak Melalui Penerapan Model Numbered Headstogether (NHT) Pada Peserta Didik Kelas I Semester Ganjil Pada MIN 11 Gunungkidul Tahun Pelajaran 2019 /2020 - Widi Qodariyani (At-Tajdid: Jurnal Ilmu Tarbiyah, 2020)
Research with the title Increasing learning activeness and learning outcomes of students in the Akidah Akhlak subject through the application of the numbered heads together (NHT) model in class I students of odd semester at MIN 11 Gunungkidul Academic Year 2019/2020 is classroom action research. What this study examines is the application of learning with the numbered heads together (NHT) model, increasing student activity and learning outcomes. This study uses observation to determine the learning process of numbered heads together (NHT), observation to determine student activity and tests to determine student learning outcomes. The results of this study indicate that the learning process using the numbered heads together (NHT) model is as follows. Stage 1 group formation, stage 2 giving member numbers, stage 3 giving assignments / questions, stage 4 group discussions, stage 5 randomly calling members, stage 6 Student presentations. The implementation from cycle 1 to cycle 2 has improved. This study shows that the activity of students from initial conditions to cycle 1 and to cycle 2 continues to increase. In the initial conditions to cycle 1 and to cycle 2 the percentage of students whose activity was in the low category continued to decline, namely 75 - 57% - 3.6%, while those in the medium category were from 20% - 26% - 41%, while those in the high category 5 -% - 25% - 50%. This study shows that student learning outcomes have increased after taking action. The percentage of students who have not completed has decreased from cycle 1 to cycle 2 (61% to 0%). The percentage of students who completed an increase from cycle 1 to cycle 2 (39% to 100%). The indicator of the success of this CAR is that this CAR is said to be successful if the percentage of students whose learning outcomes have completed reaches a minimum of 85%. And the table shows that the percentage of students whose scores have completed has reached 100%. So this PTK has been successful.